Breeding methods of Kazakhstan poplar hybrids (Experimental biology, 2020)
The combination of clonal micropropagation method with container growing allows accelerating the provision of elite planting material of poplar hybrids for forestry needs. The object of the study was poplar hybrids obtained in Kazakhstan during hybridization: Kazakhstani, 1967, Excellent, 39/64, 1/86. To obtain aseptic plants of poplar hybrids in an in vitro culture, first thoroughly washed with a soap solution, then the most effective was to use as a sterilizing agent Belizna (1:1) 10 min, 70% ethyl alcohol 5 min, 0.1% mercuric chloride (HgCl2) 5 min. Rinse thoroughly 3 times with sterile distilled water. After these procedures, 3 times were thoroughly washed with sterile distilled water. In addition to saprophytic microflora, pathogenic microflora can develop in plants, which does not die during sterilization. During cloning, the basal portion of explants, sterile from saprophytic microflora was also tested for infectious microflora using VISS medium. The Murasige and Skoog medium was optimal for intensive growth and propagation of explants of poplar shoots with a slight change: vitamin B1 0.5 mg/l, BAP cytokinin – 0.1 mg/l, gibberellic acid (HA) – 0.02 mg/l, replacement sucrose glucose 20 g/l. Intensive root (95 %) formation of shoots of poplar hybrids was noticeable on the nutrient medium Woody Plant Medium c NUC 0,2 mg/l. The shoots of all hybrids rooted 95%. The shoots showed a high survival rate when transferred in vivo to a soil substrate with a composition of 10% sand, 40% peat, 50% chernozem.Key words: poplar, micropropagation, shoots, hybrids, in vitro, in vivo introduction, explant.